Giant Primary Schwannoma of the Left Nasal Cavity and Ethmoid Sinus - Eugene Wong; Justin Kong; Lawrence Oh; Daniel Cox; Martin Forer (Case Reports in Otolaryngology)
A unilateral tumour in the nasal cavity or paranasal sinuses is commonly caused by polyps, cysts, and mucoceles, as well as invasive tumours such as papillomas and squamous cell carcinomas. Schwannomas, in contrast, are rare lesions in this area (Minhas et al., 2013). We present a case of a 52-year-old female who presented with a 4-year progressive history of mucous hypersecretion, nasal obstruction, pain, and fullness. Imaging of the paranasal sinuses showed complete opacification of the entire left nasal cavity and sinuses by a tumour causing subsequent obstruction of the frontal and maxillary sinuses. The tumour was completely excised endoscopically. Histopathology was consistent with that of a schwannoma.